Hubungan Antara Usia Ibu dan Status Paritas terhadap Kejadian Hiperemesis Gravidarum Studi Observasional Analitik di RSIA Permata Hati Kudus - Anindya Kinowneka Dewanti; Yulice Soraya Nur Intan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Hyperemesis gravidarum (HEG) is a condition characterized by severe nausea and vomiting in early pregnancy that can lead to dehydration, electrolyte imbalance, and significant weight loss. Maternal age and parity status are suspected to play a role in increasing the risk of HEG. This study aimed to determine the relationship between maternal age and parity status and the incidence of hyperemesis gravidarum at RSIA Permata Hati Kudus during the 2021–2025 period. This research was an observational analytic study with a cross-sectional design using secondary data obtained from medical records. The sample consisted of 227 pregnant women who met the inclusion and exclusion criteria. The independent variables were maternal age (at risk: <20 years or >35 years; not at risk: 20–35 years) and parity (primiparous and multiparous), while the dependent variable was the incidence of HEG. Data were analyzed using the Chi-Square test with a significance level of 0.05. The results showed a significant relationship between maternal age and the incidence of HEG (p=0.000; OR=10.452), indicating that mothers in the at-risk age group were more likely to experience HEG compared to those in the non-risk age group. In addition, there was a significant relationship between parity and the incidence of HEG (p=0.000; OR=15.66), with primiparous mothers being at higher risk of experiencing HEG compared to multiparous mothers.